2020
DOI: 10.1111/bjep.12391
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term interrelations between socio‐emotional and language competencies among preschool dual language learners in Germany

Abstract: Background Recent research has shown that socio‐emotional and language competencies are positively associated with each other. However, few studies have explored these associations for the second language competencies (L2) of young dual language learners (DLLs). Aims This longitudinal study investigated possible bidirectional associations between L2 language (expressive and receptive vocabulary) and socio‐emotional competencies among preschool DLLs. Sample The participants were 216 German DLLs (MT1 = 52.67 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 67 publications
0
16
1
Order By: Relevance
“…If DLLs have fewer interactions with SLLs, they will gain less experience with the societal language, which they need to initiate conversations and connect with others or be seen as more desirable social partners . Interestingly, Ertanir et al (2020) reported that DLL children who showed higher receptive and expressive skills in the societal language were rated more socially competent by teachers. Similarly, in a study comparing English monolinguals, English-dominant bilinguals, fluent bilinguals, non-English-dominant bilinguals, and non-English monolinguals, Han (2010) found that non-English monolingual children received the lowest teacher ratings and observational scores on interpersonal skills (e.g.…”
Section: Language Skills and Social Competence In Dllsmentioning
confidence: 99%
See 2 more Smart Citations
“…If DLLs have fewer interactions with SLLs, they will gain less experience with the societal language, which they need to initiate conversations and connect with others or be seen as more desirable social partners . Interestingly, Ertanir et al (2020) reported that DLL children who showed higher receptive and expressive skills in the societal language were rated more socially competent by teachers. Similarly, in a study comparing English monolinguals, English-dominant bilinguals, fluent bilinguals, non-English-dominant bilinguals, and non-English monolinguals, Han (2010) found that non-English monolingual children received the lowest teacher ratings and observational scores on interpersonal skills (e.g.…”
Section: Language Skills and Social Competence In Dllsmentioning
confidence: 99%
“…Mixed findings between language and social competencies have been documented primarily among SLLs, and there is still limited research among DLLs ( Ertanir et al, 2020 ;Halle et al, 2014 ). It is therefore our main goal to further our understanding of the relationship between language skills and social competence of single and dual language learning preschool-and kindergarten-age children.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies which simultaneously examined both directions of effect while controlling for children's prior level of outcomes, however, have often found different patterns of results. Some longitudinal studies demonstrated either a unidirectional association (i.e., from language to socioemotional outcomes or the other way around; Ertanir et al, 2021;Girard et al, 2017;Rose et al, 2016) or a bidirectional association between these two domains (Girard et al, 2014(Girard et al, , 2016Petersen et al, 2013), while some research could not provide evidence for a significant relation between them (e.g., Barnett et al, 2012). Notably, while children's language skills were mainly measured by vocabulary in those studies, children's socioemotional development has been assessed very differently across studies, for example, by children's positive behavior, socioemotional difficulties, or a compound indicator (i.e., aggregating various facets of socioemotional development).…”
Section: Association Between Language and Socioemotional Developmentmentioning
confidence: 99%
“…Furthermore, most of these studies did not differentiate between children with various language backgrounds, that is, some (or even all) of the children spoke a minority language other than the majority language of the society at home (e.g., Ertanir et al, 2021;Girard et al, 2014Girard et al, , 2016Girard et al, , 2017Rose et al, 2016). Given the variations in children's (majority) language skills (e.g., Hoff, 2018) or the conditions of language acquisition (e.g., bilingualism, attendance at extrafamilial ECEC), the association between language and socioemotional development might differ between children with different language backgrounds.…”
Section: Association Between Language and Socioemotional Developmentmentioning
confidence: 99%